Supporting Academic Career Pathways for Graduate Student Instructors through Targeted Educational Development - James E. Gentry; Shannon Stoker; Lesley Leach; Aimee Shouse (InSight)
This study investigated the role of Graduate Student Instructors (GSIs) in higher education and focused on their self-efficacy, pedagogical training, and performance. Given the expanding employment of GSIs and the influence of their teaching efficacy on undergraduate education, this research examined the effectiveness of a structured professional development program designed to enhance GSIs' teaching capabilities. Quantitative and qualitative methods were employed to assess GSIs' self-efficacy through surveys, exit slips, and student evaluations to gauge the educational impact. The findings indicated a notable and significant increase in GSIs' self-efficacy post-intervention, with positive feedback on teaching practices from undergraduate students. The findings underscore the importance of professional development programs in preparing GSIs for effective teaching roles, thereby improving the quality of higher education instruction and supporting the academic success of undergraduate students.